2020
DOI: 10.31234/osf.io/dcynw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The psychological wellbeing of frontline workers in the United Kingdom during the COVID-19 pandemic: First and second wave findings from the COVID-19 Psychological Research Consortium (C19PRC) Study

Abstract: Background: Extant research relating to the psychological impact of infectious respiratory disease epidemics/pandemics suggests that frontline workers are particularly vulnerable.Methods: The current study used data from the first two waves of the United Kingdom (UK) survey of the COVID-19 Psychological Research Consortium (C19PRC) Study to compare frontline workers with the rest of the UK population on prevalence estimates of depression, anxiety, and PTSD during the first week of ‘lockdown’ (Wave 1) and one m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 0 publications
3
36
0
1
Order By: Relevance
“…22 The impact on teachers appears similar to other front-line workers, with high anxiety, depression and distress levels, partly related to feelings of guilt at potentially infecting others and conflicting duties. 23 24 In addition to previously noted feasibility concerns over risk reduction measures, 25 26 we identified issues of year-group ‘bubble’ crossover and non-compliance due to forgetting and wanting to be ‘normal’/socialise and social distancing being impossible due to crowded school sites. The barriers we identified support calls for funding to help implement risk reduction measures (including hand-sanitiser, extra cleaning, free masks for all pupils and hiring extra teachers and teaching rooms so smaller class sizes can enable social distancing), 17 27 with schools reportedly spending up to £8 k each on COVID-19 risk reduction measures in early reopening of campuses.…”
Section: Discussionmentioning
confidence: 92%
“…22 The impact on teachers appears similar to other front-line workers, with high anxiety, depression and distress levels, partly related to feelings of guilt at potentially infecting others and conflicting duties. 23 24 In addition to previously noted feasibility concerns over risk reduction measures, 25 26 we identified issues of year-group ‘bubble’ crossover and non-compliance due to forgetting and wanting to be ‘normal’/socialise and social distancing being impossible due to crowded school sites. The barriers we identified support calls for funding to help implement risk reduction measures (including hand-sanitiser, extra cleaning, free masks for all pupils and hiring extra teachers and teaching rooms so smaller class sizes can enable social distancing), 17 27 with schools reportedly spending up to £8 k each on COVID-19 risk reduction measures in early reopening of campuses.…”
Section: Discussionmentioning
confidence: 92%
“…Notably, some results from population studies large enough to include subsamples of HCWs did not find that HCWs had significantly different mental health to the general population and/or noted that any differences found might be explained by demographic differences between HCWs and the general population. [6,29] Others show an increase for keyworkers (samples which included HCWs) of anxiety [28,30] and depression. [30] Similarly, systematic reviews and meta-analyses that compared results from HCW and general population studies found varied results, with some suggesting elevated risk amongst HCWs,[31,32] whilst others did not find any statistically significant difference in depression, anxiety, PTSD and psychological distress related to HCW status.…”
Section: Discussionmentioning
confidence: 99%
“… 4 However, another UK population study found significantly higher prevalence of depression, anxiety, and post-traumatic stress disorder in frontline workers (including health-care workers) compared with the general population. 5 …”
mentioning
confidence: 99%